Usage of Social Networking Sites by Students-Veterinarians who Study Operative Surgery - Stepanov, Oleksandr (Pedagogical Discourse, 2020)
The modern period of human development can be characterized as the time of intensive formation and rapid spread of Internet technologies. Thanks to the constant improvement of mobile technology, the Internet became easily accessible and united with the help of network services, most of the youth. It is social networks that have covered the whole world with their global web, providing the opportunity for groups of users to share interesting information with their mutual interests. Active users of social networks are students. Many of them try to use every opportunity to improve their professional training. Including those that open up for them social networks. This also applies to veterinarians studying surgical surgery. At the same time, today there is a lack of data on the use of social networks for educational purposes. The coverage of these issues was the purpose of the research. In the process of research, an analysis of scientific sources on the use of social networks for learning purposes was conducted. For receive data on the use of network technologies, student-veterinarians that study surgical surgery used the following sociological methods, such as surveys, observations, questionnaires. According to the obtained data, all surveyed students-veterinarians that study surgical surgery use social networks. At the same time, they prefer «Instagram» and «Facebook», twenty-five per cent use «Twitter» and one is registered in «Brainly». For educational purposes, these students most often use the video hosting YouTube and the network Facebook. The first is used as a platform for viewing a surgical video and «Facebook», mainly for reading text materials. It is also noted that the overwhelming majority of students studying operative surgery like surgery work, although half of them are not sure of their ability to do that. Implemented work opens the prospect for further research of the value of social networks in the preparation of veterinary surgeons.